The Neolithic settlement of Loc Giang on the Vam Co Dong River, southern Vietnam and its broader regional context. (June 2017) - Piper, Philip J.; Nguyen, Khanh Trung Kien; Tran, Thi Kim Quy; Wood, Rachel; Cobo Castillo, Cristina; Weisskopf, Alison; Campos, Fredeliza; Dang, Ngoc Kinh; Sarjeant, Carmen; Mijares, Armand S.B.; Oxenham, Marc; Bellwood, Peter
Abstract: Loc Giang is an early Neolithic settlement located on the east bank of the Vam Co Dong River in Long An Province, southern Vietnam. Archaeological excavations at the site have identified sequences of midden deposit, floor surfaces, postholes and hearths, suggesting that the settlement consisted of ground-built dwellings. Throughout the life of the settlement several phases of reconstruction and expansion could be discerned. A comprehensive radiometric-dating program indicates that the initial phases of activity within the excavated area started around 2000 cal. BCE and Neolithic activity continued until c. 1300 cal. BCE or slightly later. Comparisons with An Son, another mounded Neolithic settlement just 700 m to the east of Loc Giang, demonstrate that the two sites overlapped chronologically and were both constructed in similar ways. The new chronology from Loc Giang tightly brackets characteristic pottery types within the different phases of construction and has aided in refining the burial chronology at An Son. The material culture from Loc Giang and An Son is identical, specific to the Vam Co Dong River settlements, and distinctive from that recorded in sites on the Dong Nai Plain and along the coast. This suggests that, following initial settlement by agricultural populations who predominantly owed their origins to more northerly regions within East Asia, there was relatively rapid cultural and social diversification within the southern Vietnamese region.